Assessment of Occupational Safety and Health Implementation and Preventive Measures in Dry Dam Operations: A Case Study of the Sukamahi Dry Dam - Alya Sekar Hapsari; Prahasdipta Bayu Adhi K; Gian Azaria; Napitupulu Yosefino Rivaldo; Allen Kurniawan; Vicky Aswady Suryana (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Background: Dry dams serve as flood-control mechanisms in urban regions subjected to extremehydrometeorological conditions. The Sukamahi Dry Dam, the first dry dam in Indonesia, has been operationalsince 2022 and mitigates peak discharges toward Jakarta. This study assessed the implementation of occupationalhealth and safety (OHS) measures, identified potential hazards, and evaluated risk levels associated with the dam’soperational activities. Method: Hazard identification and risk assessment methodology was applied to categorize hazards and computerisk scores on the basis of consequence, exposure, and likelihood. Data collection involved field observations,interviews with 26 personnel, and a review of operational documents at the Sukamahi Dry Dam in 2024. Results: Six primary operational tasks, most notably crane hoist operations and work conducted at heights,presented significant risks, with consequence scores of 100. Major deficiencies were identified, including theabsence of fall protection systems, undocumented inspections of lifting equipment, outdated standard operatingprocedures (SOPs), and inconsistent use of protective equipment. Irregular training, the absence of safety officers,limited emergency preparedness, and a reactive safety culture exacerbate these hazards. Conclusion: Current OHS practices are inadequate for ensuring safe operations. Such practices can be improvedthrough competency-based training, the establishment of risk-based SOPs with clear standards, safety audits, improved emergency response, and the integration of digital monitoring technology to enhance worker protection and ensure the reliability of flood control measures.